Epidemiological and clinical features of asymptomatic patients with SARS‐CoV‐2 infection. Issue 10 (12th May 2020) - Xu, Tianmin; Huang, Rui; Zhu, Li; Wang, Jian; Cheng, Juan; Zhang, Biao; Zhao, Haiyan; Chen, Kang; Shao, Huaping; Zhu, Chuanwu; Wu, Chao; Liu, Longgen
Abstract: Few studies reported the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infected patients with completely asymptomatic throughout the disease course. We investigated the epidemiological and clinical features of patients infected by SARS‐CoV‐2 without any symptoms. Patients with confirmed SARS‐CoV‐2 infection were retrospectively recruited. The demographic characteristics, clinical data, treatment, and outcomes of SARS‐CoV‐2 infected patients without any symptoms were analyzed. Fifteen (4.4%) of 342 SARS‐CoV‐2 infected patients did not develop any symptom during the course of the disease. The median time from exposure to diagnosis was 7.0 days (interquartile range [IQR]: 1.0‐15.0 days). Of the 15 patients, 14 patients were diagnosed by tested positive for SARS‐CoV‐2 in throat swabs, while one patient was only tested positive for SARS‐CoV‐2 in anal swabs. During hospitalization, only 1 (6.7%) patient developed lymphopenia. Abnormalities of chest computed tomography examinations were detected in 8 (53.4%) patients on admission. As of 8 March 2020, all patients have been discharged. The median time of SARS‐CoV‐2 tested negative from admission was 7.0 days (IQR: 4.0‐9.0 days). Patients without any symptoms but with SARS‐CoV‐2 exposure should be closely monitored and tested for SARS‐CoV‐2 both in anal and throat swabs to excluded the infection. Asymptomatic patients infected by SARS‐CoV‐2 have favorable outcomes.